2020
DOI: 10.1088/1742-6596/1641/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Quality of corona.jatengprov.go.id Website Towards User Satisfaction using Webqual 4.0 Method

Abstract: This research focuses on how to measure the quality of a website using the Webqual 4.0 method, what are the factors that influence user satisfaction. The PLS-SEM technique was used to verify questionnaire data from a sample of 155 respondents. The result shows that the quality of service interaction has a significant (positive) effect of 54.2% compared to the aspect of information quality and usability quality that has no significant effect. These results indicate that the corona.jatengprov.go.id site users ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
0
0
2
Order By: Relevance
“…In actuality, though, this is inversely proportional to the findings of Nugraha et al (2020) and Haryanti and Setyorini (2019), who found that a rise in information quality will lead to a fall in user satisfaction. However, this is not surprising because the obtained coefficient value is less significant than the values of other variables, meaning an increase will not have a considerable effect.…”
Section: Correlation Between Information Quality and User Satisfactionmentioning
confidence: 95%
See 1 more Smart Citation
“…In actuality, though, this is inversely proportional to the findings of Nugraha et al (2020) and Haryanti and Setyorini (2019), who found that a rise in information quality will lead to a fall in user satisfaction. However, this is not surprising because the obtained coefficient value is less significant than the values of other variables, meaning an increase will not have a considerable effect.…”
Section: Correlation Between Information Quality and User Satisfactionmentioning
confidence: 95%
“…A study conducted by Nugraha et al (2020) and Haryanti and Setyorini (2019) research, there is little correlation between the level of user satisfaction and information quality variables. Information Quality negatively impacts user satisfaction; put another way, an increase in Information Quality will result in a decrease in user satisfaction.…”
Section: Correlation Between Information Quality and User Satisfactionmentioning
confidence: 98%
“…Mengukur mutu website menggunakan WebQual 4.0 sangat membantu dalam pengolahan Website yang menyesuaikan dengan kualitas website berdasarkan pandangan pengguna akhir [12]. WebQual telah dikembangkan pada tahun 1998 dan sudah mengalami banyak kali interaksi dalam pembangunan dimensi dan soal hingga versi saat ini [3], [13]. Analisis ini merupakan peningkatan dari ServQual Zeithaml yang banyak diperlukan dalam pengukuran jasa.…”
Section: Pendahuluanunclassified
“…Salah satu jenis evaluasi yang dapat dilakukan, yaitu evaluasi kualitas dari media E-learning Website Quality (Webqual) 4.0 merupakan salah satu instrumen evaluasi yang dapat digunakan untuk mengukur kualitas dari sebuah situs web, termasuk website media pembelajaran secara daring [9]. Webqual digunakan untuk mengukur kualitas website berdasarkan persepsi dari sudut pandang pengguna website terhadap tiga dimensi utama dari Webqual, yaitu Usability Quality, Information Quality dan Service Interaction Quality [10]- [12].…”
Section: Pendahuluanunclassified
“…Penelitian ini menggunakan pendekatan Webqual 4.0 dalam melakukan pengukuran terhadap kualitas dari sebuah Elearning. Webqual 4.0 merupakan salah satu teknik yang dapat digunakan untuk mengukur kualitas dari sebuah website, termasuk E-learning berdasarkan penilaian dari pengguna [10], [12] Dalam Webqual 4.0 terdapat beberapa langkah yang harus dilakukan hingga didapatkan hasil akhir berupa indeks kualitas dari sebuah E-learning [19], [20], antara lain :  Hitung nilai rata-rata kepentingan yang di simbolkan dengan Mol  Hitung nilai Skor maksimum Perhitungan nilai ini didapat melalui Persamaan (1).…”
Section: B Webqual 40unclassified